Correction to: Kinesins: Motor Proteins as Novel Target for the Treatment of Chronic Pain (Molecular Neurobiology, (2019), 56, 6, (3854-3864), 10.1007/s12035-018-1327-y) - Shantanu P.A.; Sharma D.; Sharma M.; Vaidya S.; Sharma K.; Kalia K.; Tao Y.-X.; Shard A.; Tiwari V. (My University, 2025)
The original version of this article unfortunately contained mistakes. Dr. Yuanxiang Tao second affiliation in this manuscript was inadvertently added. Dr. Tao has confirmed that he has no affiliation with Neuroscience Research Institute, Zhengzhou University Academy of Medical Sciences. With this, the authors agreed that this affiliation will be deleted from the proof. Dr. Vinod Tiwari missed to include his second affiliation “Department of Pharmaceutical Engineering & Technology, Indian Institute of Technology, BHU, Varanasi 221005, India” during the publication process, and this institution should be added on proof”. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.